A Country Road, Trinidad, B.W.I. - (:unkn) unknown (Muir, Marshall and Co., Trinidad, 2010)
In this photograph are images of a typical country scene in Trinidad, British West Indies. A mountain recedes into the background. The wide earthen road curves into the distance. Light poles and trees, including a few coconut palms, line the roadside. The verges of the roads are clear. The grass has been cut low. The silhouette of a man is seen sitting at the left on an embankment. A man on donkey cart near the centre of the photograph is approaching the bicycle rider.
Colour: Black and White; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Rural roads--Trinidad and Tobago; Trees--Trinidad and Tobago; Coconut palm--Trinidad and Tobago; Carriages and carts--Trinidad and Tobago; Bicycles--Trinidad and Tobago